19. THE RETROSPECTIVE ANALYSIS OF TRIGEN INTERTAN NAIL IN THE TREATMENT OF UNSTABLE INTERTROCHANTERIC FEMORAL FRACTURES AT HOSPITAL FOR TRAUMATOLOGY AND ORTHOPAEDICS (Vietnam Journal of Community Medicine, 2023)
Background: Intertrochanteric fractures is one among the most common injuries in the elderly population, 90% of which occurring in people aged over 65. This type of geriatric fracture has a relatively high mortality and causes severe impairment of function. Common treatment options for unstable intertrochantic fractures include proximal femoral nail antirotation (PFNA) and InterTan nail (IT). Due to its lower failure and good biomechanical advantage, PFNA or IT is frequently used and has attained good clinical results in the treatment of unstable intertronchanteric fracture. IT nail with the unique design of two cephalocercical screws in an intergrated mechanism, allows linear intraoperative compression and rotational stability of the neck and head fragment. We evaluate clinical results of IT in the treatment of intertrochanteric fracture in Hospital for Traumatology and Orthopedics. Objective: The aim of this study was to investigate the outcomes of the IT nail for unstable intertrochantic.Methods: Retrospective analysis, case series report. From February 2021 until August 2021, 35 patients with unstable intertrochantic fractures treated with IT nail were retrospectively evaluated. The epimiology, operative time, intraoperative blood loss, intraoperative blood transfusion, length of hospital stay, bone healing rate and complications related to the IT nail were recorded.Results: The mean age is 70,97±16,97, mean operative time is 60 minutes, mean intraoperative blood loss is 160,86±72,8 ml, mean intraoperative blood transfusion is 203,43 ± 189,29 ml , mean length of hospital stay is 7 days, 97,14% bone healing.Conclusions: Unstable intertrochanteric fractures were treated successfully with the IT nail in elderly patients. Our results demonstrate that using IT nail in the treatment of unstable intertrochanteric fractures demonstrate good clinical in terms of surgical time, intraoperative blood loss, hospital stay and union rate in elderly patients. Further study is needed to confirm these early results.
Keywords: Intertrochantic fracture, Trigen InterTan nail.